Mediation of information on eliminating violence against women - de Souza Brandão Guaraldo, Tamara [UNESP]; dos Santos, Celia Maria Retz Godoy [UNESP]; Melo, Daniele Mendes (IGI Global, 2022)
Violence against women is a central topic in the public debate in Brazil. In this way, entities and other stakeholders require flexible strategies in order to eliminate it. This chapter aims to report experiences related to an action research based on the transformative and reflexive potential of civil society groups (in Bauru city, state of Sao Paulo) involved in eliminating violence against women. In this sense, mediation of information is discussed in order to prioritize the elimination of gender-based violence against women. In face of outcomes, mediation of information have been used in order to explore the adaptative and dynamic nature of participatory methodologies by not only allowing reflective processes but also providing value of how all stakeholders present themselves as mediators by using their knowledge in order to mediate information.